THE ZINC STATUS IN CHILDREN WITH ALLERGIES: A SYSTEMATIC REVIEW AND META-ANALYSIS - Ningsih, Rusdian; Hikmah, Zahrah; Endaryanto, Anang (Universitas Airlangga, 2025)
Allergies pose significant health concerns, particularly in children, where they can adversely affect growth and quality of life. Recent studies have suggested that zinc deficiency may play a critical role in the immune dysregulation associated with allergies. The method used in This systematic review followed the PRISMA guidelines and analyzed studies on the relationship between zinc levels and allergies in children, using data from PubMed, Science Direct, EBSCO, and Cochrane Library, and a meta-analysis was conducted to evaluate the effect size and risk of bias assessed using the Newcastle-Ottawa Scale to examine the relationship between zinc levels and allergies in children. Our findings indicate that children with allergies may exhibit different zinc levels compared to healthy controls, with a pooled effect size of -0.56 (95% CI: [-0.99, -0.13]). The analysis revealed significant heterogeneity (Tau² = 0.39; Chi² = 79.41, df = 8, p < 0.00001; I² = 90%), highlighting the variability across studies and the necessity for further research to standardize the methodologies. These results were statistically significant (Z = 2.54, p = 0.01), suggesting a potential association between zinc levels and allergies in children. Further investigations are needed to explore whether zinc supplementation can support immune function and alleviate allergic symptoms.